The Edutech Platform’s Design: “Grand Huda” with a Positive Psychological Approach of the Perma Model - Hadi Alhail; Fatriana Vinola; Della Purnama; Khodijah; Chandra Sihura; Arizi Akbar; Nicolaus Ramli Bachtiar Sijabat; Adek Cerah Kurnia Azis (Gorga : Jurnal Seni Rupa, 2026)
This research aims to design and develop the edutech platform “Grand Huda” as a medium for children’s drawing and coloring, grounded in the positive psychology approach of Martin Seligman’s PERMA model (Positive Emotion, Engagement, Relationships, Meaning, Accomplishment). The study employs the Research and Development (R&D) method with the DDD-E model, which consists of the stages: decide, design, develop, and evaluate. A qualitative approach is used to explore user needs and to design learning programs aligned with the characteristics of elementary school students. The subject of the study was a 3rd grade student who participated in an online drawing and coloring program. Data collection techniques included in-depth interviews, observations, focus group discussions, and documentation. Data analysis was conducted using content analysis, involving data reduction, presentation, verification, and conclusion drawing. The findings indicate that the “Grand Huda” platform was successfully designed as an art learning ecosystem integrated with PERMA elements. The program was structured progressively through color gradation exercises, thematic drawing activities, and practice-based projects, supported by digital media such as modules, worksheets, video tutorials, and interactive online classes. Evaluation results revealed improvements in students’ drawing and coloring skills, with grades rising from sufficient to advanced categories. Beyond technical progress, students demonstrated increased motivation, confidence, and engagement in learning. Therefore, the “Grand Huda” edutech platform based on the PERMA model offers an innovative alternative for digital art education that is more humanistic, interactive, and supportive of students’ psychological well-being.